1989
DOI: 10.1099/00221287-135-1-175
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Substrates for Sulphate-reducing Bacteria within Marine and Esturaine Sediments with Different Rates of Sulphate Reduction

Abstract: The substrates used by sulphate-reducing bacteria in sediment slurries from Loch Eil, Loch Etive and the Tay estuary were determined by selectively inhibiting sulphate reduction with 20 mM-molybdate and measuring the resultant substrate accumulation. Substrate accumulation was linear after molybdate addition, and the rate of accumulation closely matched sulphate reduction rates, indicating that metabolic pathways other than those specifically involving sulphate reduction were not affected by the inhibitor. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
3
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 46 publications
6
111
3
3
Order By: Relevance
“…Acetate has been shown previously to be the most important volatile fatty acid in terms of concentration and turnover, and identified as important substrate for anaerobic terminal electron-accepting processes in marine sediments (Sørensen et al, 1981;Parkes et al, 1989;Fukui et al, 1997;Finke et al, 2007). The addition of 170 mM acetate per day to our incubations exceeded these low concentrations of acetate in the control without acetate and stimulated its mineralization (Figures 1 and 3).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Acetate has been shown previously to be the most important volatile fatty acid in terms of concentration and turnover, and identified as important substrate for anaerobic terminal electron-accepting processes in marine sediments (Sørensen et al, 1981;Parkes et al, 1989;Fukui et al, 1997;Finke et al, 2007). The addition of 170 mM acetate per day to our incubations exceeded these low concentrations of acetate in the control without acetate and stimulated its mineralization (Figures 1 and 3).…”
Section: Resultsmentioning
confidence: 78%
“…As acetate is an important electron donor for microbial iron and sulfate reduction in marine sediments (Sørensen et al, 1981;Parkes et al, 1989;Fukui et al, 1997;Finke et al, 2007), we chose ( 13 C-labeled) acetate as the substrate for RNA-SIP studies and MPN counts of manganese reducers.…”
Section: Introductionmentioning
confidence: 99%
“…During the summer-autumn period in bottom sediments of leaf litter accumulation zones under sufficient sulfate concentration, the activity of sulfate reducing bacteria was promoted due to accumulation of labile organic matter and partly because of temperature. A higher abundance of heterotrophic bacteria determined in bottom sediments of leaf litter accumulation zone in its turn could produce a greater variety of substrates for sulfate reducing bacteria (Parkes et al, 1989) and intensify SR process. In litter accumulation zone, in spite of the oxidative conditions in the near-bottom water, the abundance and activity of SRB were similar to those in profundal zone of stratified lakes with anaerobic hypolimnion (Krevs and Kucinskiene, 2012).…”
Section: Datementioning
confidence: 99%
“…However, recent investigations have shown a probable involvement (Burdige 1989, 1991, Parkes et al 1989. Smith & Klug (1981) reported that sulphate reduction accounted for 85 % of the dissolved free amino acid (DFAA) oxidation in lake sediment.…”
Section: Introductionmentioning
confidence: 99%